PENGARUH KONSERVATISME AKUNTANSI, PERTUMBUHAN PENJUALAN DAN TATA KELOLA PERUSAHAAN TERHADAP TAX AVOIDANCE - Ismanto, Juli (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to determine the effect of accounting conservatism, sales growth, and corporate governance on tax avoidance. Secondary data is sourced from the financial statements of companies included in the Consumer Non-Cyclicals index company in the Food & Beverage sub-sector listed on the IDX during the 2017-2021 period. The number of samples used was 22 companies as research objects for five years. Panel data regression analysis is used as a mechanism in this study. The results showed that accounting conservatism has a significant effect on tax avoidance. On the other hand, sales growth and corporate governance do not significantly affect tax avoidance. Therefore, it is indicated that accounting conservatism can indirectly affect tax avoidance by reducing corporate profits and producing more cautious financial statements.Keywords: Accounting Conservatism, Good Corporate Governance, Sales Growth, Tax Avoidance.